Elaboración del estudio de prefactibilidad para el montaje de una empresa para la integración y comercialización de un sistema de control de posición geográfica, velocidad y vídeo vigilancia para transporte escolar en Bogotá (2016)
The study of pre-feasibility for the “Assembly of a company for the integration and commercialization of a system of control geographical position, speed and video surveillance for school transport in Bogotá (“System of Control”) arises from need to comply with decree 348 of 2015 which promote the use of technology for the control of vehicles and drivers, which results in the improvement of road safety and the reduction of accident rates within the fulfillment of the objectives strategic partnerships of the Ministry of Transport. These objectives are aligned with global targets to reduce traffic accidents.